IMPACT OF ACTIVE IMMUNIZATION AGAINST INHIBIN, USING A SINGLE BOOSTER DOSE, ON OVULATION RATE AND FERTILITY IN LOW-PROLIFIC SIROHI GOATS - PRIYADHARSINI, R; KHARCHE, S D; GOEL, A K; JINDAL, S K; KUMAR, S (The Indian Journal of Animal Reproduction, 2022)
Five Sirohi does received primary immunization against endogenous inhibin (400 μg peptide-ovalbuminconjugate, S.C.) and five others were kept as control (400 μg ovalbumin, S.C.). All the does received a singlebooster (Immunized, 200 μg peptide-ovalbumin conjugate; control, 200 μg ovalbumin) about four weeks afterprimary immunization. Estrus was synchronized using a double injection schedule of PGF2α on days 35 and 45from the day of primary immunization. Immunization against inhibin lead to an increase in ovulation rate andcorpora lutea as indicated by plasma progesterone. The kidding percentage in immunized and control group was100% (litter size, 1.63) and 80% (litter size, 1.25), respectively. Thus, inhibin immunization with a single boosterdose can be used to improve ovarian activity and fertility in low-prolific Sirohi goats.
Keywords: Fertility; Goat; Immuno-neutralization; Inhibin; Ovulation rate